2020
DOI: 10.1080/15140326.2020.1816130
|View full text |Cite
|
Sign up to set email alerts
|

Poverty aversion or inequality aversion? The influencing factors of crime in China

Abstract: This paper aims to understand whether and how poverty aversion and inequality aversion affect the criminal behaviors. We analyze the relationship between the three variables through a theoretical model and an empirical model. The panel data of 27 provincial-level regions in China were collected for testing the hypothesis. The investigation revealed: 1. Inequality significantly increases crime, while the poverty reduction does not reduce crime. 2. The widening consumption gap between urban and rural residents m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 61 publications
0
3
0
2
Order By: Relevance
“…Earlier studies have indicated that crime rates often increase with population density (POP_DENSITY) (Song et al 2020). Crime can be understood as a conflict between people, so the greater the population density, the greater the conflict potential and the higher the crime risk (Song et al 2020). In our results, population density shows a negative impact on crime, although not significant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have indicated that crime rates often increase with population density (POP_DENSITY) (Song et al 2020). Crime can be understood as a conflict between people, so the greater the population density, the greater the conflict potential and the higher the crime risk (Song et al 2020). In our results, population density shows a negative impact on crime, although not significant.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, western and southern Europe showed that inequality had no significant effect on crime rates (Kim et al 2020). In China, Song et al (2020) showed that consumption inequality is a major driver of crimes.…”
Section: Introductionmentioning
confidence: 97%
“…Faktor ekonomi negatif menjadi insentif kriminalitas berkurang hanya jika faktor ekonomi negatif tersebut diantisipasi. Contoh faktor ekonomi negatif yang diantisipasi adalah tingkat pengangguran (Buba et al, 2018;Ishak & Bani, 2017;Khan et al, 2015), tingkat kemiskinan (Diaw et al, 2014;Opeyemi Oyelade, 2019;Pare & Felson, 2014;Song et al, 2020), dan ketimpangan ekonomi (Buba et al, 2018;Goda & Torres García, 2019;Grover, 2013;Heimer, 2019;Lobonţ et al, 2017).…”
Section: Gambar 1 Produksi Barang Legal Dan Kriminalunclassified
“…Semakin sedikit jumlah penduduk miskin, semakin sedikit jumlah kriminalitas. Sebaliknya, semakin banyak penduduk miskin, semakin banyak jumlah kriminalitas (Diaw et al, 2014;Opeyemi Oyelade, 2019;Pare & Felson, 2014;Song et al, 2020). Kecuali pada satu daerah, semua daerah di provinsi Jawa Tengah telah mengantisipasi dan menurunkan jumlah penduduk miskin dengan rata-rata penurunan jumlah penduduk miskin antara 1,1% hingga 1,4%.…”
unclassified
“…The challenges and further questions of how society has a drive about a wide variety of choices have many possibilities that can maximize added value to such assistance or are oriented toward desires that approach irrational behavior. Efforts to distribute welfare and eliminate poverty are the solution in China, which assumes that if many people are rich, the government will be easier to run compared to a government dominated by the poor (Song et al, 2020).…”
Section: Introductionmentioning
confidence: 99%